2024
DOI: 10.1007/s12144-024-05622-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of adult attachment and minority stress in isolating behaviors perpetration among lesbian and gay people in Italy

Tommaso Trombetta,
Maria Noemi Paradiso,
Lavinia Venturini
et al.

Abstract: Attention to Same-Sex Intimate Partner Violence (SSIPV) has increased in the last decades. Isolating behaviors, however, have been poorly studied, despite the increased vulnerability to isolation experienced by gay and lesbian couples. The aim of the present study was to examine the independent effects of minority stressors (experiences of discrimination, perceived stigma, and internalized homonegativity), emotion dysregulation, and adult attachment dimensions (attachment avoidance and anxiety) on isolating be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
3
1
0
Order By: Relevance
“…Specifically, both dimensions of adult attachment (anxiety and avoidance) were positively associated with internalized homonegativity. These findings are consistent with other studies on the same subject [ 25 , 26 , 27 , 28 , 30 ]. On the one hand, the association between attachment anxiety and internalized homonegativity may be explained by the tendency of individuals with higher levels of attachment anxiety to hyperactivate the attachment system.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Specifically, both dimensions of adult attachment (anxiety and avoidance) were positively associated with internalized homonegativity. These findings are consistent with other studies on the same subject [ 25 , 26 , 27 , 28 , 30 ]. On the one hand, the association between attachment anxiety and internalized homonegativity may be explained by the tendency of individuals with higher levels of attachment anxiety to hyperactivate the attachment system.…”
Section: Discussionsupporting
confidence: 94%
“…However, it is possible that in particularly stressful situations, available resources are insufficient to limit access to negative cognitions and emotions [ 41 ], thereby promoting the expression of homonegative attitudes toward the self. These data are consistent with the results found in several studies on this topic [ 26 , 27 , 28 , 30 ], although the study by Calvo et al [ 25 ] found that the relationship between attachment avoidance and internalized homonegativity was fully mediated by social support. Further studies are needed, also using more complex statistical models, as some of these relationships have only been tested at the bivariate level [ 26 , 27 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations